Criteria for evaluating studies at scientific medical events - Vieira, René Aloisio da Costa; Bonetti, Tatiana Carvalho de Souza; Marques, Marcia Maria Chiquitelli; Facina, Gil (Mastology, 2020)
Medical journals value the quality of studies. Scientific events are spaces for discussion in the face of scientific advances, innovation and consensus. In them, space is opened for the presentation of clinical studies, translational studies, experience reports and videos, with the best-designed studies being selected and awarded. The lack of clear criteria allows for differences in assessments, making it difficult to place value on situations associated with research. In order to improve quality, it is necessary to evaluate ethics, the hierarchy of scientific evidence (methodology), the study design, the originality, the relevance, and the linearity of the material presented. The present study aims to discuss these points, presenting proposals to be used in the evaluation of clinical studies, translational studies, case reports and videos in scientific medical events.